Rare Case Report - Brothers of Laurence Moon Biedl Syndrome with Guillain - Barre Syndrome (Indian Journal of Case Reports, 2016)
Laurence Moon Biedl syndrome is an autosomal recessive disorder characterized by obesity, hypogonadism, mental retardation, polydactyly, and retinitis pigmentosa. Guillain-Barre syndrome (GBS) or acute inflammatory demyelinating poly radiculo neuropathy (AIDP) is considered to be an immunological disorder with an acute and often fulminant evolution characterised by a syndrome of rapidly progressive flaccid paralysis, aflexia and albumino-cytological dissociation in the CSF. We are here with presenting case report of brothers with Laurence Moon Biedl syndrome (LBS) who presented with GBS simultaneously.